2005
DOI: 10.1039/b510145j
|View full text |Cite
|
Sign up to set email alerts
|

A new structural form for a decanuclear copper(ii) assembly

Abstract: The synthesis and structure of a novel decanuclear copper(II) cage is reported. The assembly of the cage is facilitated by the cumulative coordinative interaction of tert-butyl phosphonate, 2-pyridylpyrazole and hydroxide ligands with copper(II) ions. Magnetic studies of this decanuclear copper(II) cage indicate complex antiferromagnetic behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…[126] The use of more bulky pyrazole ligands (i.e. [141] The reaction of an iron(II) salt with the 3-(2-pyridyl)pyrazole ligand formed by the decomposition of the ligand tris[{3-(2- Figure 11. [127] The incorporation of other functional groups in the amino substituents of the pyrazole ring, such as imidazole (HL2j [125] and HL2l [128] ligands) or 1,4,7-triazacyclonanane (HL2m ligand), [129] has also been studied.…”
Section: Pyrazole Ligands With N-donor Substituents Aminesmentioning
confidence: 99%
“…[126] The use of more bulky pyrazole ligands (i.e. [141] The reaction of an iron(II) salt with the 3-(2-pyridyl)pyrazole ligand formed by the decomposition of the ligand tris[{3-(2- Figure 11. [127] The incorporation of other functional groups in the amino substituents of the pyrazole ring, such as imidazole (HL2j [125] and HL2l [128] ligands) or 1,4,7-triazacyclonanane (HL2m ligand), [129] has also been studied.…”
Section: Pyrazole Ligands With N-donor Substituents Aminesmentioning
confidence: 99%
“…This may be due to the fact that metal phosphonates have very poor solubility, so that they are frequently found in polymeric coordination complexes rather than in cage complexes. [7] Several metal phosphonate clusters have been described in recent years, including iron, [7] zinc, [8][9][10][11][12] cadmium, [13] copper, [14,15] cobalt, [16,17] manganese, [18,19] gallium, [20] tin, [21] and vanadium [22] cages, all of which exhibit intriguing structures and properties. For example, Chandrasekhar and Kingsley re- 4 ]· 7 CH 3 OH (M = Cd 1, M= Zn 2).…”
Section: Introductionmentioning
confidence: 99%
“…However, in 1997, Ward and co-workers (Jones et al, 1997) observed another coordination mode, where it acted as a tridentate bridging ligand via deprotonation of the pyrazole NH group and coordination of the pyrazole N atom to a second metal ion. The coordination chemistry of HL as a tridentate bridging ligand with Cu II cations has been studied by several researchers to date (Jeffery et al, 1997;Mann et al, 1999;Chandrasekhar et al, 2005;Hu et al, 2006), but to the best of our knowledge, only three structurally related Cu II complexes with deprotonated HL and aromatic acids have been reported (Hu et al, 2006).…”
Section: Commentmentioning
confidence: 99%